C4‐Selective Synthesis of Vinyl Thiocyanates and Selenocyanates Through 3, 4‐Dihalo‐2(5H)‐furanones. Issue 28 (25th June 2019) - Wu, Han‐Qing; Yang, Kai; Luo, Shi‐He; Wu, Xin‐Yan; Wang, Neng; Chen, Si‐Hong; Wang, Zhao‐Yang
Abstract : In the absence of a metal catalyst and under the promotion of sodium bicarbonate, an eco‐friendly and practical protocol for the synthesis of vinyl thiocyanate derivatives through the reaction of 3, 4‐dihalo‐2(5 H )‐furanones with KSCN at room temperature has been developed. This method has a broad substrate scope and is suitable for gram‐scale synthesis (up to 5 g). Importantly, it can also be used to synthesize vinyl selenocyanate derivatives. Abstract : An environmental‐friendly protocol enables the synthesis of vinyl thiocyanates and selenocyanates from 3, 4‐dihalo‐2(5 H )‐furanones, including low‐reactive Csp2‐Cl, substrates in the absence of a metal catalyst and under the promotion of simple inorganic base sodium bicarbonate.